(untitled) (Educational Dimension, 2022)
The model of the formation of realistic professional aspirations of future psychologists, aimed at implementation in master’s programs of specialist training is presented in the article. Methodological approaches that form the basis of the specified model are determined: personal-oriented, system-strategic, resource-based, competence-environmental. The possibilities of integration of future psychologists into the professional environment by the method of informal education are presented through the implementation of pedagogical interaction strategies: interaction with stakeholders; activity of a training seminar on employment problems and master classes on self-presentation training of future psychologists in the job search process; individual consultations on the organization of reflection on the results of real employment. It has been made the conclusions about the expediency of highlighting the presented theoretical foundations of the proposed model for the formation of realistic professional aspirations in future psychologists.